The influence of democratic leadership style and organizational culture on employee job satisfaction in the Lamongan Regency government - Hidayat, Firman Nur; Santoso, Moh.Heru Budi; Novitasari, Diah Ayu; Purnomo, Nanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human resources (HR) are very important for the entire management of an organization because they facilitate the achievement of their goals. At present, it is very important for the leaders of the business world and government to be able to adapt to existing policies. Various modifications occur in the work environment of subordinates. The purpose of this writing is to test the potential for the synergistic impact of organizational culture and democratic leadership styles on employee job satisfaction in the Lamongan Regency government environment. Assessment of validity and reliability, evaluation of classical assumptions, multiple linear regression analysis, evaluation of the coefficient of determination, T and F tests, and the domination test all entered into this composition. The results of this writing show that organizational culture and democratic leadership styles have a significant influence on employee job satisfaction.